Habib Syech Assegaf's Preaching Strategy on Social Media: A Review Through Hovland's Response Theory - Intan Muharni; Bukhori Bukhori; Nurseri Hasnah Nasution (Bulletin of Indonesian Islamic Studies, 2025)
Preaching through social media is a new phenomenon among Indonesian society, especially for Gen-Z. Habib Syech Assegaf is a contemporary cleric who has a moderate da'wah school, he provides Islamic values ​​to the wider community through social media. This study examines the da'wah strategy of Habib Syekh Assegaf on social media reviewed through the Response, Stimulus, Organism, Response (SOR) theory proposed by Hovland. This study aims to determine and describe the understanding, attention, and acceptance of Habib Syech Assegaf's Da'wah Response on social media, in more detail the purpose of this study is whether the da'wah can be accepted by society, especially Gen-Z. The response consists of attention, understanding and acceptance. The research method used is qualitative based on literature studies, with data analysis obtained from primary sources (the Qur'an, hadith and related literature) and secondary sources (academic journals, scientific books and the latest research related to the theme). Research findings based on the review of Hovland's Theory, Habib Syech Assegaf's da'wah strategy on social media has proven effective in attracting attention, facilitating understanding, and encouraging acceptance of messages by the audience. The three components of Hovland's Response Theory can be found clearly in his communication patterns on social media, making social media a relevant and impactful means of da'wah in today's digital era.